THE INFLUENCE OF PRICE AND SERVICE QUALITY ON PURCHASE DECISIONS MEDIATED BY BRAND IMAGE(Study on Bittersweet by Najla Consumers on ShopeeFood in Denpasar City) - Made Githa Prawisanti; I Putu Gde Sukaatmadja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to explain the influence of price and service quality on purchase decisions mediated by brand image of Bittersweet by Najla on ShopeeFood in Denpasar City. The research was conducted on ShopeeFood users in Denpasar City with a sample size of 108 respondents. The sample was determined using purposive sampling and collected through offline questionnaires. Data were analyzed using SPSS 27. The results of hypothesis testing show that price has a positive and significant effect on purchase decisions. Service quality has a positive but not significant effect on purchase decisions. Price has a positive and significant effect on brand image. Service quality has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchase decisions. Price has a positive and significant effect on purchase decisions through the mediation of brand image. Service quality has a positive and significant effect on purchase decisions through the mediation of brand image.